Environmental Protection for Sustainable Development: A Study of the Pilkada Debate in Aceh from a Legal Policy Perspective - Efendi, Efendi; Zuhri, M.; Salsabila, Syifa (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Environmental protection is a very important issue in the Sustainable Development Goals (SDGs) including Indonesia. Because the main requirement for development is based on maintained natural resources such as clean and affordable energy, handling climate change, marine and terrestrial ecosystems. However, the global environmental crisis with uncertain climate change threatens the future of the world and humanity. The purpose of this study is to determine whether environmental protection for sustainable development can be accommodated in legal policies through the 2024 Aceh Pilkada debate. This study uses an empirical methodwith a legal policy approach. Data were collected by means of literature studies and interviews, the literature reviewed was laws, regulations, journal articles andbooks related to the focus of discussion, while the informants interviewed were members of the House of Representatives and the Environmental Service. The results of this study conclude that environmental protection for sustainable development is something that is very urgent. Because sustainable development in the future is largely determined by how seriously the state maintains its environment inIndonesia. Furthermore, environmental issues in Aceh are complex problems thatrequire comprehensive and sustainable solutions that can be implemented in government policies. In the context of legal policy, the role of the government asthe main actor in implementing legal regulations, supported by the active participation of all stakeholders, and influencing the legal behavior of the community and the private sector, is very necessary to realize Aceh in sustainable development.